Comorbidity Mechanism and Management of Chronic Low Back Pain and Major Depressive Disorder: From Neural Circuit Remodeling to Precision Medicine - Lin Faqu; Lin Chenjuan; Xiang Xiangyin; Li Xin (Brain and Behavior, 2026)
ABSTRACT Objective This review systematically elaborates multi‐system interactive mechanisms underlying comorbid chronic low back pain (CLBP) and major depressive disorder (MDD), synthesizes recent advances in diagnosis, treatment, and management, and proposes precision medicine directions to address clinical challenges, including missed diagnosis, treatment resistance, and poor prognosis. Method We reviewed 86 studies published between 2015 and 2025 from the PubMed, Embase, and CNKI databases. We focused on basic research and clinical trials, integrating multi‐omics data to construct mechanistic frameworks and therapeutic evidence. Result The comorbid pathogenesis of CLBP and MDD is driven by dysregulation of the “neural–immune–endocrine–gut–brain axis” network. Spinal dorsal horn N‐methyl‐D‐aspartate (NMDA) receptor NR2B phosphorylation amplifies pain signals 2‐ to 3‐fold, while anterior cingulate cortex (ACC)–insula connectivity correlates positively with depression severity. Microglial toll‐like receptor 4/nuclear factor‐κB (TLR4/NF‐κB) activation increases cerebrospinal fluid interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) by 3.2‐ and 2.7‐fold, respectively. Hypothalamic–pituitary–adrenal (HPA) axis dysfunction causes a flattened cortisol rhythm, with glucocorticoid receptor gene (NR3C1) hypermethylation reducing glucocorticoid sensitivity by 45%. Gut dysbiosis decreases short‐chain fatty acids (SCFAs) by 30% and increases plasma lipopolysaccharide (LPS) by 2.3‐fold, accompanied by abnormal proliferation of pro‐inflammatory E. coli and Desulfovibrio as well as depletion of anti‐inflammatory Prevotella . Duloxetine reduces visual analog scale (VAS) pain scores by 40% and Hamilton Depression Rating Scale (HAM‐D) scores by 35% relative to placebo. Closed‐loop spinal cord stimulation (SCS) improves treatment response rates to 68% compared with open‐loop stimulation. Electroacupuncture at BL23/LR3 alleviates clinical symptoms in 75% of patients relative to sham acupuncture. At the 12‐month follow‐up, duloxetine's pain relief efficacy slightly declined from 40% to 38%, a phenomenon speculated to be linked to serotonin transporter upregulation. At the 1‐year follow‐up, closed‐loop SCS efficacy decreases to 55%, which may be associated with secondary neural circuit re‐remodeling. At the 6‐month follow‐up, electroacupuncture treatment carries a 22% symptom recurrence rate, which researchers hypothesize arises from secondary gut microbiota re‐dysbiosis featuring reduced Prevotella abundance. Conclusion Pathological progression of concurrent CLBP and MDD relies on multi‐level remodeling of molecular, cellular, and systemic biological networks. Precision interventions targeting neural circuits, neuroinflammation, and the gut–brain axis, combined with multidisciplinary clinical collaboration, represent core strategies to break through current diagnostic and therapeutic bottlenecks.